Curtobacterium flaccumfaciens pv. Flaccumfaciens detection in bean seeds using a semi-selective culture medium - Maringoni, Antonio Carlos [UNESP]; de Cassia Camara, Renata (Soc Brasileira Microbiologia, 2006)
The bacterial wilt caused by Curtobacterium flaccumfaciens pv. flaccumfaciens is currently considered one of the most important bacterial bean disease in Brazil. One of the most effective control methods against this disease is the use of healthy seeds. However, no methods are known that could be routinely used to detect this bacterium in bean seeds under Brazilian condition. The aim of this work was to evaluate qualitative and quantitative detection methods for Curtobacterium flaccumfaciens pv. flaccumfaciens in naturally-infected bean seeds, and the detection of this pathogen in thirty bean seed samples, by sowing onto a semi- selective culture medium the leachate obtained from soaked bean seeds. Both the qualitative and quantitative methods were effective for detecting the presence of the bacteria in the seeds samples analysed. The qualitative method proved more practical for rotine use; of the thirty bean seed samples analyzed by this method, fifty percent were infected with Curtobacterium flaccumfaciens pv. flaccumfaciens.
Keywords: bacterial wilt; isolation; seed pathology; Phaeolus vulgaris